UPAYA PENDIDIKAN DALAM MEMBENTUK SOSOK MANUSIA YANG SEUTUHNYA - Weni Yulastri; Dutika Handayani; Emi Sofia; Salsabila; Elmasi Tri Oktaviani; Fenri Naldi (STKIP Subang, 2025)
Education plays a crucial role in shaping holistic human beings who possess balanced intellectual, emotional, social, physical, and spiritual competencies. This article explores various educational efforts that support the formation of whole-person development, including character building, social emotional learning (SEL), intellectual empowerment, and moral spiritual cultivation. Using a literature review method, this study concludes that holistic human development requires integrated strategies that involve schools, families, and communities. Effective and continuous collaboration among these educational ecosystems will optimally shape students who are intelligent, ethical, resilient, and ready to face the challenges of the 21st century.